2013
DOI: 10.1007/s11427-013-4491-3
|View full text |Cite
|
Sign up to set email alerts
|

Environmental connections of novel avian-origin H7N9 influenza virus infection and virus adaptation to the human

Abstract: A novel H7N9 influenza A virus has been discovered as the causative identity of the emerging acute respiratory infection cases in Shanghai, China. This virus has also been identified in cases of infection in the neighboring area Hangzhou City in Zhejiang Province. In this study, epidemiologic, clinical, and virological data from three patients in Hangzhou who were confirmed to be infected by the novel H7N9 influenza A virus were collected and analyzed. Human respiratory specimens and chicken feces from a conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
83
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 17 publications
2
83
0
1
Order By: Relevance
“…Agriculture sector argues that the H7N9 does not cause any diseases for poultry therefore it should not be called avian influenza virus. Whereas Li et al [4] unambiguously demonstrated the relatedness of human infection with poultry or poultry related market. The question can be open for further discussion and we also need to see the circulation trends of the virus in the future.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Agriculture sector argues that the H7N9 does not cause any diseases for poultry therefore it should not be called avian influenza virus. Whereas Li et al [4] unambiguously demonstrated the relatedness of human infection with poultry or poultry related market. The question can be open for further discussion and we also need to see the circulation trends of the virus in the future.…”
mentioning
confidence: 99%
“…Unlike the highly pathogenic H5N1 virus, which kills the birds [1-3], H7N9 is avirulent to either domestic poultry or migratory birds, which makes the situation even worse as it is hard to identify the birds who carry the viruses. In this issue of SCIENCE CHINA Life Sciences, Li et al [4] present solid evidence that the human infecting H7N9 viruses are directly from the live free markets, where some patients visited before falling ill. In accordance with a report in The Lancet [5], the work also shows the avian-signature sequences from the environment where chickens are kept in the free market and human-signature sequences in the patients, implying the in-vivo micro-evolution and host adaptation during the outbreak and infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A single reoccurring case was just reported on 15 October, in Zhejiang Province, China. Until now, there have been no confirmed cases of human-to-human transmission, and most infected humans had a history of contact with poultry or of having visited a wet market [2][3][4][5][6] , although suspected human-to-human transmission has been described 7 . Our previous analyses on the first released virus genomes proposed that this virus might have emerged from at least four origins by means of genetic reassortment 3 .…”
mentioning
confidence: 99%
“…According to the epidemiology and sequence analyses, H7N9 virus-contaminated live-poultry markets (LPM) are regarded as the major sources of the human infections with the H7N9 virus (6)(7)(8). Therefore, after the initial report of H7N9 influenza virus infection in humans in March 2013, environmental sampling programs and enhanced sentinel hospital surveillance were implemented in Guangdong in order to identify possible cases of infection and to analyze the evolution of the virus.…”
mentioning
confidence: 99%